International economics - Eicher, Theo S. (Routledge, 2009)
Thought-provoking and clearly explained, the new edition provides students of international economics and international business with a rigorous explanation of global economic theory and policy, both current trends and historic developments. It explores key models through case studies and review questions, enabling students to challenge the reporting of economic events by press and government alike. Split into 2 parts – International Trade and International Finance – the text explains conceptual building blocks before applying them to current events and controversies. Key issues discussed include: